2008
DOI: 10.1080/19315860801988228
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Adults with Autism with and without Co-morbid Psychiatric Disorders: Differences in Maternal Well-Being

Abstract: This study investigated the associations between the characteristics of adolescents and adults with autism spectrum disorders (ASD) and maternal well-being. Two groups were compared: mothers of adolescents and adults with ASD and co-morbid psychiatric disorders (n = 142) and mothers whose sons or daughters had a single diagnosis of ASD (n = 130). Individuals with co-morbid psychiatric disorders had higher levels of repetitive behaviors, asocial behavior, and unpredictability of behavior than their counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 55 publications
3
27
4
Order By: Relevance
“…Past research has explored possible reasons for the elevated levels of psychological distress observed among parents of children with ASD, documenting several contributing factors including the core symptoms of autism (e.g., social difficulties, communication difficulties, and repetitive behaviors), delays in adaptive behavior, and co-occuring physical and mental health problems (Bishop et al, 2007; Cadman et al, 2012; Kring et al, 2008, 2010; Tomanik, Harris, & Hawkins, 2004). The majority of studies have consistently found that challenging behavior problems are among the most significant sources of stress for families (Hastings et al, 2005; Herring et al, 2006; Lounds, Seltzer, Greenberg, & Shattuck, 2007), highlighting how educational interventions to address child behavior likely will have cascading benefits for family life and parent stress.…”
Section: The Needs Of Families During Transitionmentioning
confidence: 99%
“…Past research has explored possible reasons for the elevated levels of psychological distress observed among parents of children with ASD, documenting several contributing factors including the core symptoms of autism (e.g., social difficulties, communication difficulties, and repetitive behaviors), delays in adaptive behavior, and co-occuring physical and mental health problems (Bishop et al, 2007; Cadman et al, 2012; Kring et al, 2008, 2010; Tomanik, Harris, & Hawkins, 2004). The majority of studies have consistently found that challenging behavior problems are among the most significant sources of stress for families (Hastings et al, 2005; Herring et al, 2006; Lounds, Seltzer, Greenberg, & Shattuck, 2007), highlighting how educational interventions to address child behavior likely will have cascading benefits for family life and parent stress.…”
Section: The Needs Of Families During Transitionmentioning
confidence: 99%
“…Co-occurrence of sleep problems in ASD is high, 2930 with some evidence linking sleep problems to high rates of hyperactivity, anxiety, depression, mood swings, or aggression in ASD. 31 High rates of GI problems also have been documented in children with ASD 32 and have been linked to psychiatric comorbidity 33 , anxiety, irritability, social withdrawal, and rigid-compulsive symptoms. 3435 Self-injurious behavior (SIB) and aggressive behavior have also been linked to the co-occurrence of mood disorders in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when faced with aggressive behaviour, parents may have a greater sense of burden and be more likely to use multiple medications. It is well known that parents report greater distress in the presence of child behaviour and mental health problems (Cadman et al 2012;Kring et al 2008;Lin 2011;Schieve et al 2007), and that mental health problems are associated with greater medication use. It remains an intriguing possibility that parent burden may influence the decision to medicate, but more refined measures of aggressive behaviour, behaviours targeted with medication, and the decision to medicate are required to better understand the inter-relationships between these child and parent variables.…”
Section: Parent Variablesmentioning
confidence: 99%
“…Parent circumstance may also play a role in prescription patterns. Research suggests that parents of children with ASD face significant caregiving burden (Cadman et al 2009;Kring et al 2008;Lin 2010), and that when families are in crisis they, and healthcare providers, may turn to medication as a solution (Mackintosh et al 2012;Weiss et al 2009). There are a number of possible parent factors that could contribute to this decision, including parent demographic variables (e.g., marital status, age, education) and parent psychological functioning (e.g., burden, crisis).…”
mentioning
confidence: 99%